Occurrence, Antibiotic Resistance, and Population Diversity of Listeria monocytogenes Isolated From Fresh Aquatic Products in China - Chen, Moutong; Cheng, Jianheng; Wu, Qingping; Zhang, Jumei; Chen, Yuetao; Xue, Liang; Lei, Tao; Zeng, Haiyan; Wu, Shi; Ye, Qinghua; Bai, Jianling; Wang, Juan (Frontiers in Microbiology, 2018)
Listeria monocytogenes is an important Gram-positive foodborne pathogen. However, limited information is available on the comprehensive investigation and potential risk of L. monocytogenes in fresh aquatic products, which are popular to consumers in China. This study aimed to determine the occurrence, virulence profiles, and population diversity of L. monocytogenes isolated from aquatic products in China. In total, 846 aquatic product samples were collected between July 2011 and April 2016 from 43 cities in China. Approximately 7.92% (67/846) aquatic product samples were positive for L. monocytogenes, 86.57% positive samples ranged from 0.3 to 10 MPN/g, whereas 5.97% showed over 110 MPN/g by the Most Probable Number method, which included two samples of products intended to be eaten raw. Serogroups I.1 (serotype 1/2a), I.2 (serotype 1/2b), and III (serotype 4c) were the predominant serogroups isolated, whereas serogroup II.1 (serotype 4b) was detected at much lower frequencies. Examination of antibacterial resistance showed that nine antibacterial resistance profiles were exhibited in 72 isolates, a high level susceptibility of 16 tested antibiotics against L. monocytogenes were observed, indicating these common antibacterial agents are still effective for treating L. monocytogenes infection. Multilocus sequence typing revealed that ST299, ST87, and ST8 are predominant in aquatic products, indicating that the rare ST299 (serotype 4c) may have a special ecological niche in aquatic products and associated environments. Except llsX and ptsA, the 72 isolates harbor nine virulence genes (prfA, actA, hly, plcA, plcB, iap, mpl, inlA, and inlB), premature stop codons (PMSCs) in inlA were found in four isolates, three of which belonged to ST9. A novel PMSC was found in 2929-1LM with a nonsense mutation at position 1605 (TGG→TGA). All ST87 isolates harbored the ptsA gene, whereas 8 isolates (11.11%) carried the llsX gene, and mainly belonged to ST1, ST3, ST308, ST323, ST330, and ST619. Taken together, these results first reported potential virulent L. monocytogenes isolates (ST8 and ST87) were predominant in aquatic products which may have implications for public health in China. It is thus necessary to perform continuous surveillance for L. monocytogenes in aquatic products in China.